Peran Supervisi Kepala Sekolah Dalam Mewujudkan Profesionalisme Guru di MI Muhammadiyah Program Khusus Kartasura - Aisyah Mirawati, Nur; , Drs. Saring Marsudi, SH. M.Pd (2017)
This study aims to (1) describe the role of principal supervisory activities in realizing the professionalism of teachers in MIM PK Kartasura. (2) to describe the obstacles of the Supervising in MIM PK Kartasura. (3) to describe the solution of barriers of Supervising implementation in MIM PK Kartasura. This type of research is qualitative descriptive. The research was conducted at MI Muhammadiyah PK Kartasura. Data collection techniques used were interviews, observation, and documentation. Resource persons in this research are principal as main informant, as well as vice principal and teacher as teaching staff at the school. Based on the research, it can be concluded (1) The result of the research suggests the role of principal supervision in realizing the professionalism of the teacher by conducting scheduled supervision, unscheduled supervision with supervised fields are teaching and learning activities, lesson plan, teacher creativity in class display, teacher's personality and neatness. (2) the barriers to the implementation of Supervision in MIM PK Kartasura is the schedule of teacher supervision along with other activities, the lack of adequate teaching aids, and the difficulty in determining teacher strategy in learning. (3) the solution of the barriers to the implementation of Supervision in MIM PK Kartasura is by replacing the teacher's supervision schedule that is unable to teach, innovating by making media / props, and consulting the preparation of the lesson plan with the deputy headmaster.